Municipal solid waste compost: Global trends and biogeochemical cycling - Xiaoxia Cao; Paul N. Williams; Yuanhang Zhan; Scott A. Coughlin; John W. McGrath; Jason P. Chin; Yingjian Xu (Elsevier, 2023)
Municipal solid waste (MSW) compost is being prioritised as a sustainable solution for urban waste management and is increasingly being used by agriculture as a soil enhancer, quasi-fertiliser and carbon mitigation tool. Here, we examine these changes and the growing global use of MSW compost and discuss its expanding adoption and application across different world regions. Factors influencing the composition of MSW compost, including processing technologies as well as feedstock characteristics such as seasonality, source variation, and maturation regimes, are discussed. An analysis of advantages and disadvantages of MSW compost is presented. The benefits are considered from the perspective of interplays within carbon, nitrogen and phosphorus cycles, and emerging roles in pollutant remediation. Conversely, the potential risks such as the presence of toxic elements, microplastics, and persistent organic pollutants, and impacts on greenhouse gas emissions are also examined. The production of high-quality MSW compost is underpinned by the selection and screening of appropriate feedstock. However, there are increasing opportunities for production technologies, which improve physical, chemical, and biological traits of the composts to the point that they can also provide phyto-stimulant/protection services. However, there is little information on the use of MSW compost in forestry. Overall, this review provides a comprehensive overview of the global trends, composition factors, advantages and disadvantages, strategies for efficient use, and future perspectives of MSW compost utilisation. It highlights the importance of balanced decision-making that considers both environmental and economic factors to maximise the potential benefits of MSW compost for sustainable waste management and soil improvement.